CbfA, the C-Module DNA-Binding Factor, Plays an Essential Role in the Initiation of Dictyostelium discoideum Development - Winckler, Thomas (American Society for Microbiology, 2004)
We recently isolated from Dictyostelium discoideum cells a DNA-binding protein, CbfA, that interacts in vitro with a regulatory element in retrotransposon TRE5-A. We have generated a mutant strain that expresses CbfA at <5% of the wild-type level to characterize the consequences for D. discoideum cell physiology. We found that the multicellular development program leading to fruiting body formation is highly compromised in the mutant. The cells cannot aggregate and stay as a monolayer almost indefinitely. The cells respond properly to prestarvation conditions by expressing discoidin in a cell density-dependent manner. A genomewide microarray-assisted expression analysis combined with Northern blot analyses revealed a failure of CbfA-depleted cells to induce the gene encoding aggregation-specific adenylyl cyclase ACA and other genes required for cyclic AMP (cAMP) signal relay, which is necessary for aggregation and subsequent multicellular development. However, the cbfA mutant aggregated efficiently when mixed with as few as 5% wild-type cells. Moreover, pulsing cbfA mutant cells developing in suspension with nanomolar levels of cAMP resulted in induction of acaA and other early developmental genes. Although the response was less efficient and slower than in wild-type cells, it showed that cells depleted of CbfA are able to initiate development if given exogenous cAMP signals. Ectopic expression of the gene encoding the catalytic subunit of protein kinase A restored multicellular development of the mutant. We conclude that sensing of cell density and starvation are independent of CbfA, whereas CbfA is essential for the pattern of gene expression which establishes the genetic network leading to aggregation and multicellular development of D. discoideum.